ЕЛЕКТРОЕНЕРГЕТИЧНА СИСТЕМА ЯК ОБ'ЄКТ НЕЛІНІЙНОЇ ЕЛЕКТРОЕНЕРГЕТИКИ - Авраменко, В.Н. (Інститут електродинаміки Національної академії наук України, 2017)
Electric power system is a highly nonlinear dynamic system. Comparison of analytical and numerical methods of stability analysis of nonlinear systems is full execution. By calculations on the test scheme for the cross section of the West-Vinnitsa IPS of Ukraine, it is shown that to check its stability "in the small" may not be sufficient analysis of the linearized model of power system.As a small disturbance, it was decided to cut 5% of the load of the powerful substation of the Kiev energy center. The automatic regulator of excitation of a strong action which actually is installed at the station was taken into account for the generator of the block number 2 of Khmelnitsky NPP. The load was taken into account by the static characteristics of voltage and frequency. For repair conditions of IPS of Ukraine, there may be situations when the effects of automatic regulation of excitement of  generators leads to oscillation mode parameters and risk of violation of stability of the ECO. Efficient numerical solution of the problem of sustainability of EES in the program of the Institute of electrodynamics of NAS of Ukraine ATS-74, numerical-analytical algorithms which take into account the features of the EPS as nonlinear systems, allows to analyze not only the dynamic stability, but static stability of the EPS by computing the transient process at small finite perturbation. Referenses 6, figures 6.